Supination Adduction Vertical Medial Malleolar Fracture Fixation with Buttress Plating vs a Novel Screw-Only Construct: A Cadaveric Biomechanical Study. (June 2022) - Testa, Edward J.; Walsh, Devin; Patel, Devan; Kahan, Lindsey G.; Modest, Jacob; Schilkowsky, Rachel; Hsu, Raymond
Background: Supination adduction ankle fractures are unique among rotational ankle fractures as plate constructs are more commonly used than independent screws for medial malleolar fixation. The purpose of this study was to compare fracture displacement between plate fixation to a novel screw-only construct using a cadaveric biomechanical early-weightbearing model for the treatment of vertical medial malleolus fractures. Methods: Six nonosteoporotic fresh-frozen cadaver shanks and feet in matched pairs underwent a vertical osteotomy of the medial malleolus to simulate the supination adduction type injury. Osteoporosis was measured using DEXA scans. One specimen from each pair was fixed with a one-third tubular buttress plate and the other with screw-only fixation. The specimens were then axially loaded for 100 000 cycles to simulate protected weightbearing, and subsequently loaded to failure in supination. Stiffness, fracture displacement, and load to failure were recorded. Statistical significance was set at P <.05. Results: There were no measurable differences in displacement between the 2 constructs during axial cyclic loading after 100 000 cycles (plate, 0.74 ± 0.09 mm; screws, 0.79 ± 0.18 mm; P = .225). During supination and axial load to failure, the plate outperformed the screw construct. For load to failure (2 mm displacement) at the fracture site, the plate group failed at 716 ± 240 N, whereas the screw group failed at 567 ± 237 N ( P = .015). During load to catastrophic failure, the plate group outperformed the screw group (plate, 6011 ± 1646 N; screws, 4578 ± 1837 N; P = .002). Conclusion: For vertical medial malleolar fractures, the screw-only construct demonstrated no statistical difference when compared to buttress plating for cyclical axial loading, simulating early weightbearing in a boot. However, buttress plating is 21% to 24% stronger than the screw-only fixation construct in overall strength and prevention of catastrophic failure when loading in a supinated position. Clinical Relevance: The screw-only construct is biomechanically similar to a buttress plate when simulating early protected weightbearing. This suggests that early weightbearing as tolerated in a controlled ankle motion boot beginning 2 weeks postoperatively is mechanically safe for this fracture pattern and does not result in unacceptable amounts of fracture displacement. This construct may be useful as a less invasive treatment modality for the treatment of vertical medial malleolus fractures in select patients.